Reoperation following strabismus surgery among Medicare beneficiaries: Associations with geographic region, academic affiliation, surgeon volume, and adjustable suture technique - Christensen, Michael R (Indian J Ophthalmol, 2018)
PURPOSE: The objective of this study was to determine the associations of strabismus surgery reoperation rates in a large national database of provider payments with geographic region, practice type and volume, and the availability of adjustable suture technique. METHODS: Fee-for-service payments to providers for medicare beneficiaries having strabismus surgery between 2012 and 2015 were retrospectively analyzed to identify reoperations in the same calendar year. The adjustable-suture technique was considered to be available to the patient if the patient's surgeon billed for adjustable sutures. Predictors of reoperation in the same calendar year were determined by multivariable logistic regression. RESULTS: Availability of the adjustable suture technique was not associated with reoperation rate in multivariable analysis among 5971 patients having horizontal muscle surgery (odds ratio, [OR] 0.86, P = 0.29), 2840 patients having vertical muscle surgery (OR 0.98, P = 0.93), or 1199 patients having surgery with scarring or restriction (OR 0.86, P = 0.61). For horizontal surgery, the reoperation rate was higher in academic practices (OR 1.67), as compared with community practices, and in the South (OR 2.85) and West (OR 1.92, all P < 0.001). The reoperation rate was unchanged with surgeons in the lowest-quartile of surgical volume. Among surgeons paid for horizontal surgery, 45% of surgeons in the Northeast, the West, or Florida coded for adjustable sutures, compared with 8% of surgeons elsewhere (P < 0.001). CONCLUSION: The availability of the adjustable-suture technique was not associated with reoperation rate after strabismus surgery in this large national database. Having surgery by a lower-volume surgeon was not associated with a higher reoperation rate. The reoperation rate was higher when surgery was conducted in an academic practice, or in certain regions of the country. Adjustable sutures are largely a bicoastal practice.